Les récits de la bioéconomie comme grille de lecture des tensions sur les transformations écologiques du capitalisme - Nicolas Béfort; Pascal Grouiez; Romain Debref; Franck-Dominique Vivien (Revue de la Régulation)
This article provides an understanding of the ecological transition as a new phase of capitalism. We adopt a meso-regulation approach and propose to think of the patterns of ecological transition as the outcome of a confrontation among heterogeneous groups of actors. We focus on the case of the bioeconomy, whose specific feature lies in its capacity to question the institutionalization of some material and energy flows. We discuss the contribution of the bioeconomy, as a meso-economic space still under construction, to the definition of an ecological form of capitalism. Using a definition of meso spaces as spaces of differentiation within capitalism, we question the ability of the bioeconomy to contribute to the reconfiguration of the accumulation regime, applying it to the case of France. We demonstrate the existence of three narratives of the meso spaces of the bioeconomy (biotechnology bioeconomy, biorefinery bioeconomy and ecological bioeconomy). These narratives contribute to defining the meso space of the bioeconomy. They are in tension over how they conceive material flows and the territorialization and sectoralization of the biobased economy.